The role of bivalent ions in the regulation of D-loop extension mediated by DMC1 during meiotic recombination - Altmannova, Veronika; Spirek, Mario; Orlic, Lucija; Jēkabsons, Atis; Clarence, Tereza; Henggeler, Adrian; Mlcouskova, Jarmila; Chaleil, Raphaël A G; Matos, Joao; Krejci, Lumir (iScience, 2022)
During meiosis, programmed DNA double-strand breaks (DSBs) are repaired by homologous recombination. DMC1, a conserved recombinase, plays a central role in this process. DMC1 promotes DNA strand exchange between homologous chromosomes, thus creating the physical linkage between them. Its function is regulated not only by several accessory proteins but also by bivalent ions. Here, we show that whereas calcium ions in the presence of ATP cause a conformational change within DMC1, stimulating its DNA binding and D-loop formation, they inhibit the extension of the invading strand within the D-loop. Based on structural studies, we have generated mutants of two highly conserved amino acids - E162 and D317 - in human DMC1, which are deficient in calcium regulation. In vivo studies of their yeast homologues further showed that they exhibit severe defects in meiosis, thus emphasizing the importance of calcium ions in the regulation of DMC1 function and meiotic recombination.
Keywords: Cell biology; Structural biology